Global partnerships in nursing – A qualitative study in lessons for success. (July 2021) - Morley, Dawn A.; Cunningham, Sheila
Abstract: Global nursing partnerships can develop cultural competence and standardisation across international nurse education programmes. Issues of context, cultural awareness and modes of engagement can influence the success of international collaboration. The 'Supporting Internationalisation of Traineeships in the Healthcare Sector' project, funded from 2017, brought together nine international partners from Finland, Poland, Spain and the UK to develop a pan-European quality audit process for clinical learning environments. As part of the evaluation, eight project partners were interviewed about the project and their criteria for a successful global partnership. The interviews allowed insight into previously hidden aspects of implementation. The importance of a scoping period for nursing global partnerships was highlighted that built on cultural diversity to explore common understandings. Attention to the use of prior expertise in internationalisation, or project objectives, could accelerate a global partnership to achieve a greater potential in its outcomes and cultural sensitivity. Framed in a clear structure, it is possible for global partnerships to embed ownership, autonomy and individual voice in partner organisations. The research concludes that only by growing international champions through funded and well constituted projects, that a genuine impact on the global health and educational needs in nursing can be met. Highlights: There is a lack of guidance on what constitutes a successful nursing global partnership. A scoping period builds on cultural diversity to explore common understandings. The use of prior international expertise enhances outcomes and cultural sensitivity Ownership, autonomy and individual voice can be structured into partnership working.